PERAN GURU DALAM MENERAPKAN NILAI TANGGUNG JAWAB SISWA MELALUI MEDIA AUDIO-VISUAL PADA PEMBELAJARAN KEWARGANEGARAAN KELAS V SD - Indah Cahyani; Bukman Lian; Syska Purnama Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Responsibility is an important character value that must be instilled in students from an early age. This study aims to analyze the role of teachers in implementing student responsibility values ​​through audio-visual media in Citizenship Education (PKn) learning in grade V of SD 92 Palembang. The method used is a quantitative approach with data collection through questionnaires distributed to students. The results of the analysis show an Asymp. Sig value of 0.000, indicating a significant influence of the role of teachers in implementing student responsibility values, because the sig value is less than 0.05. These findings indicate that the use of audio-visual media not only improves students' understanding of citizenship material, but also contributes to the development of character and values ​​of responsibility. This study is expected to contribute to the development of more innovative and effective learning strategies, as well as being a reference for teachers in increasing student involvement in the learning process.